The Influence of Transformational Leadership and Organizational Culture as Mediation on Employee Performance at Ciawi Regional Hospital - Rozikin, Khoirul; Nurdin, Boy (Cognitionis Civitatis et Politicae, 2025)
This study aims to analyze the influence of transformational leadership on employee performance with organizational culture as a mediating variable at Ciawi Regional General Hospital (RSUD Ciawi). A quantitative approach was employed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The sample was determined using Slovin's formula, resulting in 120 respondents consisting of RSUD Ciawi employees. Data were collected through structured questionnaires and analyzed using SEM-PLS software. The results revealed that transformational leadership positively and significantly affects employee performance (Hypothesis 1). Organizational culture also positively and significantly influences employee performance (Hypothesis 2). Furthermore, organizational culture effectively mediates the relationship between transformational leadership and employee performance, with a positive and significant effect (Hypothesis 3). These findings indicate that a strong organizational culture can enhance the impact of transformational leadership in improving employee performance. The practical implications of this study emphasize the importance of adopting transformational leadership styles and strengthening organizational culture to enhance employee performance. RSUD Ciawi management is encouraged to develop leadership programs that promote communication, motivation, and innovation while consistently implementing organizational cultural values. This study contributes theoretically to the literature on transformational leadership, organizational culture, and employee performance, particularly in the context of regional hospitals. Future research is recommended to explore other variables that may mediate or moderate these relationships, such as work motivation or job satisfaction.